A qualitative exploration of principals’ transformational leadership and transactional leadership behaviors during the COVID-19 crisis: the rise of integrated crisis leadership - Sheena, Dan; Benoliel, Pascale; Berkovich, Izhak (Frontiers in Education, 2025)
PurposeThe study seeks to provide insights into the specific leadership behaviors employed by school leaders to navigate the complex challenges posed by the pandemic.MethodsA qualitative research approach was adopted, involving in-depth interviews with a diverse sample of 20 school principals. Thematic analysis was employed to identify recurring patterns in their narratives addressing leadership styles and behaviors.FindingsThe findings vividly portray school principals’ leadership behaviors during the COVID-19 crisis. This study connected these behaviors with the characteristics of transformational and transactional leadership styles. Behaviors identified as transformational leadership emerged as the most prominent during the crisis. The research found that there is an expression for each of these characteristics in practice and demonstrated this through quotes from school principals.DiscussionTaken together, the findings show that principals viewed integrated leadership as crucial and effective during the COVID-19 crisis. This research contributes to the literature by offering a nuanced understanding of how school principals leveraged both transformational and transactional leadership behaviors during an unprecedented crisis.